The cosmopolitanism reader - Brown, Garrett Wallace; Held, David (Cambridge, UK : Polity, 2010)
In response to a renewed cosmopolitan enthusiasm, this volume brings together 25 essays in the development of cosmopolitan thought by distinguished cosmopolitan thinkers and critics. It looks at classical cosmopolitanism, global justice, culture and cosmopolitanism, political cosmopolitanism and cosmopolitan global governance.
Kant and contemporary cosmopolitanism. Idea of a universal history with a cosmopolitan purpose / Immanuel Kant -- Kant and cosmopolitanism / Martha C. Nussbaum -- Kant's cosmopolitanism / Garrett Wallace Brown -- A Kantian approach to transnational justice / Onora O'Neill -- Cosmopolitan global justice. Justice and international relations / Charles R. Beitz -- International society from a cosmopolitan perspective / Brian Barry -- Cosmopolitanism and sovereignty / Thomas Pogge -- International distributive justice / Simon Caney -- Cosmopolitanism, nationality, states and culture. Patriotism and cosmopolitanism / Martha C. Nussbaum -- What is cosmopolitan? / Jeremy Waldron -- Nationalism and cosmopolitanism / Kok-Chor Tan -- Global distributive justice and the state / Simon Caney -- Cosmopolitan politics. The cosmopolitan manifesto / Ulrich Beck -- Principles of cosmopolitan order / David Held -- Moving from cosmopolitan legal theory to legal practice: modes of cosmopolitan law / Garrett Wallace Brown -- A political constitution for the pluralist world society? / Jurgen Habermas -- Cosmopolitanism, global issues, and governance. Reframing global governance: apocalypse soon or reform! / David Held -- The architecture of cosmopolitan democracy / Daniele Archibugi -- Humanitarian intervention: towards a cosmopolitan approach / Mary Kaldor -- The environment, global justice and world environmental citizenship / Patrick Hayden -- Cosmopolitan examinations and critiques. Cosmopolitanism / David Miller -- The problem of global justice / Thomas Nagel -- On cosmopolitanism / Jacques Derrida -- Can international organizations be democratic? a skeptic's view / Robert A. Dahl -- Citizenship in an era of globalization / Will Kymlicka -- A comprehensive overview of cosmopolitan literature / Garrett Wallace Brown and Megan Kime.
Includes bibliographical references (p. [444]-464) and index.
Keywords: Cosmopolitanism